The Relationship between Symptom Flare of Atopic Dermatitis and Airborne Japanese Cedar and Cypress Pollen Counts: A Self-Scoring Diary Study. (9th April 2012) - Nishie, Haruko; Kato, Mariko; Kato, Shiori; Odajima, Hiroshi; Shibata, Rumiko; Nishima, Sankei; Kishikawa, Reiko; Koto, Eiko; Furue, Masutaka
Abstract : Background . With an increase in Japanese cedar and cypress (JC) pollinosis, the relationship between JC pollen and atopic dermatitis (AD) has been studied. Some reports suggest that JC pollen can be one exacerbating factor for AD, but there has been no report that discusses JC pollen counts relating to AD symptom flare although actual airborne JC pollen counts can widely fluctuate throughout the pollen season. Objective . The relationship between symptom flare of AD and airborne JC pollen counts was examined. Methods. We monitored JC pollen counts in real time and divided the counts into low and high level. We then analyzed self-scored "itch intensity" recorded by 14 AD patients through a self-scoring diary. Results . Among the 14 patients, 7 had significantly higher itch intensity while the pollen counts were high. Conclusion . Even during the pollen season, actual airborne pollen counts can widely fluctuate. Our study suggested that symptom flare of AD could be influenced by the actual pollen counts.